Реактивный ионно-лучевой синтез тонких пленок HfO2 - Зырянова, А С. (БНТУ, 2020)
The effect of the composition of the working gas, the substrate temperature and the target potential and characteristics of thin films of hafnium dioxide on a silicon substrate, obtained by reactive ion-beam sputtering of a metal target, has been studied. It has been established that with an increase in the partial pressure of oxygen from 2.52•10–2 to 5.85•10–2 Pa, the dielectric constant decreases by almost 2 times. The transmission and absorption of the films only slightly depend on the composition of the working gas. The band gap is equal to 5.63 eV. With an increase in the substrate temperature, the dielectric constant increases, but at the same time the dielectric losses sharply increase, and a decrease in the specific volume resistance is also observed. Moreover, an increase in the substrate temperature to 573 K leads to a deterioration in the optical characteristics. There is a decrease in transmission and an increase in absorption in the range 450–800 nm. These processes can be associated with the desorption of oxygen from the growing HfO2 film. At a target potential of Ut = 40–80 V, a significant decrease in dielectric losses occurred, and at Ut = 40 V, a sharp increase in the specific volume resistance (almost 5 times) was observed, which indicates an intensification of the interaction between oxygen and hafnium.